Interest of the preventive and curative use of defibrotide on the occurrence and severity of sinusoidal obstruction syndrome after hematopoietic stem cell transplant in children. Issue 3 (31st May 2022) - Rudebeck, Carl J.; Renard, Cécile; Halfon‐Domenech, Carine; Ouachée‐Chardin, Marie; Philippe, Michael; Valla, Frederic V.; Bertrand, Yves; Penel‐Page, Mathilde
Abstract: Defibrotide (DF) is indicated for the treatment of severe sinusoidal obstruction syndrome (SOS) following hematopoietic stem cell transplantation (HSCT), but its prophylactic use against SOS is not recommended yet. This study describes the impact of the preventive and curative use of DF on reducing the incidence and severity of SOS in children. Patients aged 0–19 years, who received allogenic HSCT after myeloablative conditioning regimen with busulfan or total body irradiation in our comprehensive cancer center, between 2013 and 2017, were included. The Baltimore or modified Seattle criteria were used for SOS diagnosis. SOS was graded using the 2017 European Society for Blood and Marrow Transplantation classification defining severity criteria of SOS in children. SOS occurrence tended to decrease with prophylactic DF, but no significant difference was observed in terms of severity. When not treated with preventive DF, 50% (19/38) of the patients with SOS were graded severe to very severe, but only 37% (7/19) had organ dysfunction. Curative DF was administered at a median of 2 days post‐HSCT, for a median of 6.5 days. The absence of fatal SOS supports the use of early curative DF with acceptable toxicities and questions the optimal duration of DF treatment.